2010
DOI: 10.1074/jbc.m110.136408
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Scramblase 1 Is Secreted by a Lipid Raft-dependent Pathway and Interacts with the Extracellular Matrix Protein 1 in the Dermal Epidermal Junction Zone of Human Skin

Abstract: We examined the interaction of ECM1 (extracellular matrix protein 1) using yeast two-hybrid screening and identified the type II transmembrane protein, PLSCR1 (phospholipid scramblase 1), as a binding partner. This interaction was then confirmed by in vitro and in vivo co-immunoprecipitation experiments, and additional pull-down experiments with GST-tagged ECM1a fragments localized this interaction to occur within the tandem repeat region of ECM1a. Furthermore, immunohistochemical staining revealed a partial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Interestingly, PLSCR1, being a signal peptide-less protein (like FGF1), is secreted through a lipid raft-dependent nonclassical pathway (Merregaert et al, 2010). We performed a series of experiments to assess the potential role of PLSCR1 in the stress-induced export of FGF1 from differentiated U937 cells, which express this protein at higher levels than do undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PLSCR1, being a signal peptide-less protein (like FGF1), is secreted through a lipid raft-dependent nonclassical pathway (Merregaert et al, 2010). We performed a series of experiments to assess the potential role of PLSCR1 in the stress-induced export of FGF1 from differentiated U937 cells, which express this protein at higher levels than do undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the SlyX domain is present in other proteins (HS3ST/heparan sulfate proteoglycans and PLSCR1 [phospholipid scramblase 1]), and these proteins are reportedly secreted via the unconventional secretory pathways. 38,39 We will, in a future study, try to identify the binding partner on the SlyX domain of IDE, and establish whether such a structure may confer a protective effect to IDE during lysosomal degradation. In this study, we found that IDE might be a substrate for the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…While PLSCRs are palmitoylated for membrane anchoring [3], TULPs are tethered to membranes by binding to phosphatidylinositol 4,5-bisphosphate [26,27]. TULP1 and Scr1, both of which have no signal peptide sequence, are secreted to the extracellular space by a mechanism different from the conventional ER (endoplasmic reticulum)–Golgi pathway, and they bind to the MerTK receptor for phagocytosis and to ECM1 (extracellular matrix protein 1) in HaCaT keratinocytes, respectively [2830]. Although secretion of Scr1 is abrogated by depletion of membrane cholesterol and has been suggested to occur via a lipid raft-dependent mechanism, the secretory mechanisms are not yet clear.…”
Section: Introductionmentioning
confidence: 99%